The Jackson jive: Blackface today and the limits of whiteness in Australia - Stratton, Jon (European Association for Studies on Australia, 2011)
Blackface has had something of a renaissance in the United States. There it is invested with a postmodern, selfconsciously parodic quality. In Australia there has also been a renaissance of blackface. Here, however, it appears to continue to be invested more straightforwardly with racism. This article focuses on the notorious Jackson Jive sketch on Hey, Hey It's Saturday in 2009. In that sketch six men blacked up and wore cheap Afro wigs performing as if they were the Jackson Five. They claimed that the sketch was simply humorous. Australians were divided; many found the sketch offensive while many considered it enjoyable. A similar division in the population occurred when Sam Newman, an ex-Australian Rules footballer and knock about comedian, blacked up in 1999 and pretended to be the Indigenous footballer, Nicky Winmar. In Australia blackface continues to reinforce the privileges of whiteness-even when, as was the case with the members of the Jackson Jive, most were in Australian terms either non-white or marginally white. In this case, blackface reinforced these men's honorary whiteness.